2017
DOI: 10.1177/2165079917704447
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Skin Disease Prevention: An Educational Intervention for Hairdresser Cosmetology Students

Abstract: Cosmetologists frequently develop occupational skin disease related to workplace exposures. The purpose of this study was to evaluate an educational intervention to increase cosmetology students' occupational skin disease knowledge and use of preventive practices. A quasi-experimental design was used to evaluate students' knowledge, behaviors, intentions, expectancies, and expectations. A 20-minute verbal presentation and printed two-page educational handout were provided for participants. Statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Occupational contact dermatitis (OCD) represents up to 48.3% of workrelated diseases with different percentages in relation to insurance system characteristics. 1,2 One of the most affected occupations is the hairdressing profession, 3 due to workplace exposure to multiple of sensitizing substances and irritating agents 4,5 in combination with wet work known to induce or aggravate other skin disorders. 6,7 Wet work, including frequent hand and hair washing, damp hair handling, and glove wearing, is the most frequent irritant exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Occupational contact dermatitis (OCD) represents up to 48.3% of workrelated diseases with different percentages in relation to insurance system characteristics. 1,2 One of the most affected occupations is the hairdressing profession, 3 due to workplace exposure to multiple of sensitizing substances and irritating agents 4,5 in combination with wet work known to induce or aggravate other skin disorders. 6,7 Wet work, including frequent hand and hair washing, damp hair handling, and glove wearing, is the most frequent irritant exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A study based on the PRECEDE–PROCEED model was found to be an effective method to prevent HE, and evidence-based practices were integrated into the HPM and the SHP program, which was similarly effective (Santer et al, 2014). Many randomized controlled studies indicate that clinical assessment of participants should be performed by a specialist, referred to as the “gold standard” (Bregnhoj et al, 2012; Haughtigan et al, 2017; Mauro et al, 2017). Thus, an important aspect of this study is the clinical examination of the severity of HE symptoms and model-based multiple interventions and educational program application.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of studies describe the effect of protective glove usage on HE symptoms in young individuals working in high-risk occupations. The studies found that the use of powdered and latex-containing gloves is not preferred for long-term use because of the side effect of increased skin symptoms (Flyvholm et al, 2005; Haughtigan et al, 2017; Oreskov et al, 2015). Side effects are eliminated with the use of nitrile and powder-free gloves, which reduce skin disease symptoms (Steengaard et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this research are parallel to the studies that have been conducted by previous researchers [62], [63], which they found that HBP have a lack of self-confidence to communicate with the customers. High level of self-confidence can help the cosmetology students to communicate well when interacting with the customers [35], [38], [67]. The cosmetology students need to have high self-confidence as they need to provide quality beauty treatment and consultation services to the customers [13], [65].…”
Section: The Factors That Influence the Competency Level Of Communica...mentioning
confidence: 99%
“…Among the factors that cause they have lack of communication skills in the workplace is their weakness in mastering the basic knowledge or theory in cosmetology field [35] and incompetency to transfer the learned theories into a practical form [9]. Whereas, the skills of transferring theory into the practical form will indirectly help in increasing the level of self-confidence among the cosmetologists to communicate with their clients better [38]- [40]. In addition, among the factors that cause the cosmetology students to have a weak level of proficiency in communication skills is they rarely use the basic words to describe something towards their customers [36], [41], [42].…”
Section: Introductionmentioning
confidence: 99%